Sply regulation of sphingolipid signaling molecules is essential for Drosophila development. - Herr, D.R.; Fyrst, H.; Phan, V.; Heinecke, K.; Georges, R.; Harris, G.L.; Saba, J.D. (Development, 2003)
Sphingosine-1-phosphate is a sphingolipid metabolite that regulates cell proliferation, migration and apoptosis through specific signaling pathways. Sphingosine-1-phosphate lyase catalyzes the conversion of sphingosine-1-phosphate to ethanolamine phosphate and a fatty aldehyde. We report the cloning of the Drosophila sphingosine-1-phosphate lyase gene (Sply) and demonstrate its importance for adult muscle development and integrity, reproduction and larval viability. Sply expression is temporally regulated, with onset of expression during mid-embryogenesis. Sply null mutants accumulate both phosphorylated and unphosphorylated sphingoid bases and exhibit semi-lethality, increased apoptosis in developing embryos, diminished egg-laying, and gross pattern abnormalities in dorsal longitudinal flight muscles. These defects are corrected by restoring Sply expression or by introduction of a suppressor mutation that diminishes sphingolipid synthesis and accumulation of sphingolipid intermediates. This is the first demonstration of novel and complex developmental pathologies directly linked to a disruption of sphingolipid catabolism in metazoans.